Hebella plana Ritchie 1907 - ÁLVARO L. PEÑA CANTERO (Zenodo, 2017)
Hebella plana Ritchie, 1907 (Fig. 9) Hebella plana— Totton, 1930: 156–157, fig. 12a, b; Peña Cantero et al. , 2004: 2290–2291 (synonymy); Peña Cantero, 2008: 454; 2010b: 766; 2014a: 1718, fig. 2g, h. Hebella striata var. plana — Jäderholm 1926: 4. Material examined. Stn 53, several hydrothecae on Staurotheca densa , S. nonscripta, and Staurotheca sp. (MNCN 2.03/539); Stn 67, a few hydrothecae on S. nonscripta and Halecium exaggeratum Peña Cantero, Boero & Piraino, 2013 (NIWA 117499); Stn 108, two hydrothecae on Antarctoscyphus spiralis (Hickson & Gravely, 1907) (NIWA 117500); Stn 126, six hydrothecae on Staurotheca densa (MNCN 2.03/540); Stn 139, a few hydrothecae on Staurotheca nonscripta (NIWA 117501); Stn 140, several hydrothecae on Staurotheca nonscripta and S. dichotoma Allman, 1888 (NIWA 117502); Stn 148, a few hydrothecae on S. nonscripta (MNCN 2.03/541); Stn 178, a few hydrothecae on Staurotheca compressa Briggs, 1938 (NIWA 117503). Remarks. In the material from Stn 178 some hydrothecae seem to emerge from within hydrothecae of Staurotheca compressa . In the material from Stn 67, on Halecium exaggeratum , there are shorter hydrothecae (Fig. 9 A) with small pedicels (680 µm high and 220 µm diameter at aperture, and 90 µm diameter at diaphragm), along with typical hydrothecae (1000–1200 µm high and 280–300 µm diameter at aperture, and ca. 100 µm diameter at diaphragm) (Fig. 9 B–C). Ecology and distribution. Shelf species (Peña Cantero et al. 2004) found at depths between 92 (Peña Cantero 2008) and 722 m (Peña Cantero et al. 2004); present material from 159 to 405 m, epibiotic on Antarctoscyphus spiralis , Halecium exaggeratum , Staurotheca compressa, S. densa, S. dichotoma and S. nonscripta . Antarctic-Patagonian distribution (Peña Cantero et al. 2004). Recently reported from off Livingston and Trinity islands (Peña Cantero 2008) and Peter I Island (Peña Cantero 2010b), in West Antarctica, and off Queen Mary Coast (Peña Cantero 2014a), in East Antarctica. See Peña Cantero et al. (2004) for previous ...